Американская мечта Сергея Есенина - Popiel-Machnicki, Wawrzyniec; Osiewicz, Bartosz (Studia Rossica Posnaniensia, 2019)
The present paper is an attempt to interpret the works of Esenin, which were created under the influence of his journey to the United States of America in 1922 and 1923. The considerations are focused on the discussion about culture and civilization in the cultural aspect of Russia and America. The polemics between Esenin and Mayakovski has also been emphasized as the Black Man’s author’s foreign trip was to a large extent motivated by his willingness to prove his poetic superiority over the outstanding futurist.